The C-X-C Motif Chemokine Ligand 5, Which Exerts an Antioxidant Role by Inducing HO-1 Expression, Is C-X-C Motif Chemokine Receptor 2-Dependent in Human Prostate Stroma and Cancer Cells - Kang-Shuo Chang; Syue-Ting Chen; Shu-Yuan Hsu; Hsin-Ching Sung; Wei-Yin Lin; Ke-Hung Tsui; Yu-Hsiang Lin; Chen-Pang Hou; Horng-Heng Juang (Antioxidants)
While the C-X-C motif chemokine ligand 5 (CXCL5) is recognized as an inflammatory mediator and a potent attractant for immune cells, its functions within the human prostate remain unclear. This study explored the expression, functions, and regulatory mechanisms of CXCL5 in prostate stroma and cancer cells. CXCL5 secreted from prostate cancer cells enhanced neutrophil migration. CXCL5 induced cell proliferation and invasion of prostate cancer cells in vitro and tumorigenesis in a xenograft animal model. C-X-C motif chemokine receptor 2 (CXCR2) has been identified on the surface of prostate fibroblasts and cancer cells. The supernatant of LNCaP cells or CXCL5 overexpression enhanced the migration and contraction of prostate myofibroblast WPMY-1 cells; however, pretreatment with SB225002, a CXCR2 inhibitor, can reverse these effects. CXCL5 evinces antioxidant properties by upregulating heme oxygenase-1 (HO-1) to counteract H2O2-induced reactive oxygen species (ROS) in a CXCR2-dependent manner in WPMY-1 and prostate cancer cells. Our findings illustrate that CXCL5, through HO-1, plays a role in antioxidation, and determine that the CXCL5/CXCR2/HO-1 pathway facilitates antioxidative communication between fibroblasts and cancer cells in the prostate. Therefore, targeting the CXCL5/CXCR2 signaling pathway could provide a new strategy for managing oxidative stress within the prostate.